ІНФОРМАЦІЙНА КУЛЬТУРА ЯК ФАКТОР ФОРМУВАННЯ ПЕДАГОГІЧНОЇ МАЙСТЕРНОСТІ (Педагогіка вищої та середньої школи, 2004)
The article deals with the problems of information culture, it shows factors that influence on the level of pédagogie skill.